Basic treatment principles for psychotic disorders in patients with epilepsy. (4th March 2013) - Adachi, Naoto; Kanemoto, Kousuke; de Toffol, Bertrand; Akanuma, Nozomi; Oshima, Tomohiro; Mohan, Adith; Sachdev, Perminder
Summary: In patients with epilepsy, coexisting psychoses, either interictal (IIP) or postictal (PIP), are associated with serious disturbance in psychosocial function and well‐being, and often require the care of a specialist. Unfortunately, evidence‐based treatment systems for psychosis in patients with epilepsy have not yet been established. This article aims to propose concise and practical treatment procedures for IIP and PIP based on currently available data and international consensus statements, and primarily targeting nonpsychiatrist epileptologists who are often the first to be involved in the management of these complex patients. Accurate and early diagnosis of IIP and PIP and their staging in terms of acuity and severity form the essential first step in management. It is important to suspect the presence of psychosis whenever patients manifest unusual behavior. Knowledge of psychopathology and both individual and epilepsy‐related vulnerabilities relevant to IIP and PIP facilitate early diagnosis. Treatment for IIP involves (1) obtaining consent to psychiatric treatment from the patient, whenever possible, (2) optimization of antiepileptic drugs, and (3) initiation of antipsychotic pharmacotherapy in line with symptom severity and severity of behavioral and functional disturbance. Basic psychosocial interventions will help reinforce adherence to treatment and should be made available. Due consideration must be given to patients' ability to provide informed consent to treatment in the short term, with the issue being revisited regularly over time. Given the often prolonged and recurrent nature of IIP, treatment frequently needs to be long‐term. Treatment of PIP consists of two aspects, that is, acute protective measures and preventive procedures in repetitive episodes. Protective measures prioritize the management of risk in the early stages, and may involve sedation with or without the use of antipsychotic drugs, and the judicious application of local mental health legislation if appropriate. As for preventative procedures, optimizing seizure control by adjusting antiepileptic drugs or by surgical treatment is necessary.